Pengaruh Posisi Peletakan Ikan Terhadap Sirkulasi Udara Dingin Di Cool Box Pada Kapal Purse Seine Menggunakan Computational Fluid Dynamics (CFD) - Urip Prayogi; Nor Sa'adah; Rafid Gifa Muhammad (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
The potential of Indonesian marine commodities is quite promising, one of which is fish. Handling treatment is very important and absolutely applied before capture, during capture, transport and distribution, processing, marketing and shipping. The placement of fish is very important to the quality of the fish and the effectiveness of the cooling system in the cool box. Fishermen usually put fish carelessly into the hold/cool box, this is very likely to reduce the quality of the catch. So it is necessary to take action to reduce the decline in fish quality and maximise cooling in the cool box. This study aims to determine the effect of fish placement model variations on cold air circulation in the cool box on a purse seine vessel using Computational Fluid Dynamics (CFD). There are two variations of the model used, namely variation model 1 (fish placement position aligned longitudinally) and variation model 2 (fish placement position arranged crosswise). Modelling using Rhinocheros software, then numerical simulation using Computational Fluid Dynamics (CFD). Numerical simulation results show the best velocity contour is in model 1 with the highest velocity of 22 m/s and temperature distribution shows the temperature contour at points 1, 2 and 3 there is a decrease in temperature 271 K (-2ºC), 268 K (-5ºC) and 266 K (-7ºC).